Spatiotemporal phosphoregulation of Lgl: Finding meaning in multiple on/off buttons. Issue 2 (3rd March 2016) - Moreira, Sofia; Morais-de-Sá, Eurico
ABSTRACT: Intracellular asymmetries, often termed cell polarity, determine how cells organize and divide to ultimately control cell fate and shape animal tissues. The tumor suppressor Lethal giant larvae (Lgl) functions at the core of the evolutionarily conserved cell polarity machinery that controls apico-basal polarization. This function relies on its restricted basolateral localization via phosphorylation by aPKC. Here, we summarize the spatial and temporal control of Lgl during the cell cycle, highlighting two ideas that emerged from our recent findings: 1) Aurora A directly phosphorylates Lgl during symmetric division to couple reorganization of epithelial polarity with the cell cycle; 2) Phosphorylation of Lgl within three conserved serines controls its localization and function in a site-specific manner. Considering the importance of phosphorylation to regulate the concentration of Lgl at the plasma membrane, we will further discuss how it may work as an on-off switch for the interaction with cortical binding partners, with implications on epithelial polarization and spindle orientation.